The underground library : a novel [large type] - Ryan, Jennifer (Jennifer L.) (Random House Large Print, 2024)
"On the day Juliet Lansdown reports to work for the first time at Bethnal Green Library, it isn't the bustling hub she's been expecting. But in the face of German attacks, she's determined to make it a place where all of their neighbors feel safe and welcome. Katie Upwood is thrilled to be working at the library too, though she's only there until she heads off to university in the fall. But after the death of her beau on the front lines and unexpected family strife, she's more in need of support than ever. Sofie Baumann, a Jewish refugee without any family to lean on, finds comfort and friendship in Bethnal Green's quickly growing literary community and escapes to the library every chance she gets. But her asylum in London is tied to a domestic work visa issued by an unscrupulous employer, leaving her vulnerable and uncertain where to turn when her work environment becomes unbearable. So when a slew of bombs damage the library, Juliet can't bear to give up on her safe haven of books and relocates the stacks into an Underground station where the city's residents shelter nightly, determined to keep lending out stories that will keep spirits up. But tragedy after tragedy strikes, threatening to unmoor the women and sever the ties of their community. Will Juliet, Kate, and Sofie be able to overcome their own troubles to save the library? Or will the beating heart of their neighborhood be lost forever?"--